2012
DOI: 10.1074/jbc.m111.321349
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Phosphorylation Protects Glycogen Synthase Kinase-3β from Calpain-mediated Truncation of Its N and C Termini

Abstract: Background: GSK-3␤ is a key pro-apoptotic kinase, and its activity is strictly regulated. Results: GSK-3␤ is cleaved at both N and C termini by calpain. Conclusion: N-or C-terminal truncation activates GSK-3␤, and Ser-9/Ser-389 phosphorylation protects GSK-3␤ from calpain cleavage. Significance: The GSK-3␤ C terminus functions as an autoinhibitory domain, and Ser-9/Ser-389 phosphorylation and calpainmediated cleavage operate together in regulating GSK-3␤ activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…N-terminal truncation eliminates the regulatory domain that inhibits the catalytic activity (Goni-Oliver et al, 2007;Ma et al, 2012). Thus, the present results seem to propose that during excitotoxicity processes there is an increase in GSK3 activity.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…N-terminal truncation eliminates the regulatory domain that inhibits the catalytic activity (Goni-Oliver et al, 2007;Ma et al, 2012). Thus, the present results seem to propose that during excitotoxicity processes there is an increase in GSK3 activity.…”
Section: Discussionmentioning
confidence: 51%
“…However, the calpain inhibitor calpeptin inhibits GSK3 truncation in cultured neurons and hippocampal slices suggesting that GSK3 is substrate only of calpain. In fact, it has been reported that the caspase-3 inhibitor Z-VAD-FMK does not prevent the generation of GSK3 truncated fragments in rat cerebellar granule neurons (Ma et al, 2012). In addition, in the same KA injected rat model, caspases are not involved in GSK3 decreased levels (Araujo et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations